Quality of work life in action : managing for effectiveness - Stein, Barry (New York, N.Y. : AMA Membership Publications Division, American Management Associations, 1983)
This book offers a framework for action and some guidelines about the kinds of things that can help raise both quality work life.
"2293"--P. [4] of cover.
Bibliography: p. 74.
ucj 17/01/2019
Loans
Keywords: Quality of work life; Labor productivity